ادارة الابتكار التربوي لتطوير المناهج التعليمية باستخدام التقنيات الحديثة من وجهة نظر مديري المدارس الأبتدائية في محافظة بغداد (Journal of the College of Basic Education, 2025)
In light of the transformations the world is witnessing in various fields, educational institutions are facing the problem of keeping pace with developments and using modern working methods, especially in administrative work. In light of the technological revolution the world is witnessing that has encompassed all aspects of life, especially educational institutions, systems are forced to make radical changes in their administrative methods. Innovation management is one of the most important modern trends and concepts that has become indispensable and has imposed itself strongly and is considered one of the most important ways to develop educational curricula. Given the leadership and administrative role enjoyed by the director through the direct connection between faculty members and students, it is necessary to bring about a qualitative development in educational curricula This study aims to analyze the role of educational innovation management in developing educational curricula using modern technologies from the perspective of school principals in Baghdad. A descriptive analytical methodology was applied to a sample of 100 school principals in Baghdad, with a questionnaire used as the main tool for data collection. The study aimed to understand the views of school principals on how modern technologies are used in curriculum development and to measure the impact of these technologies on educational quality. The study found that significant improvements have been made in curriculum development through educational innovation, but challenges remain concerning infrastructure and training for using these technologies. The study also emphasized the need to enhance professional training for principals and teachers in using technology effectively. It recommended updating curricula to incorporate modern technologies more comprehensively and strengthening technical and administrative support to sustain these initiatives.